Metabolic Study of Benzamidenafil using Liquid Chromatography Quadrupole Time-of-Flight Mass Spectrometry - Pyo, Jaesung (Current Pharmaceutical Analysis, 2022)
Background: Various illegal phosphodiesterase-5 (PDE5) inhibitors have been indiscriminately added to food and dietary supplements since the early 2000s without evaluating their side effects or pharmaceutical effects. Objective: The metabolic pathway of benzamidenafil was evaluated using liquid chromatography quadrupole time-of-flight mass spectrometry (LC-Q-ToF-MS). Methods: In vitro metabolic samples were prepared using human liver microsomes, and in vivo metabolic samples were obtained from drug-administered rats. The metabolic samples were extracted to remove biological interferences and injected into the LC-Q-ToF-MS system for analysis. Their mass spectra and chromatograms were compared and interpreted. Results: A total of nine metabolites were evaluated in the benzamidenafil-treated samples. All error values were within 5 ppm with high accuracy. Conclusion: These newly identified metabolites of benzamidenafil could be used to construct relevant legal databases and applied to related forensic cases.
Keywords: forensic toxicology